2012
DOI: 10.1143/jjap.51.111002
|View full text |Cite
|
Sign up to set email alerts
|

Individual Roles of Atoms and Ions during Hydrogen Plasma Passivation of Surface Defects on GaN Created by Plasma Etching

Abstract: In the recovery of photoluminescence intensities for band-edge emissions at around 3.47 eV in the case of gallium nitride (GaN), we have studied the individual roles of hydrogen atoms (H) and hydrogen ions (H n +). Surface defects such as nitrogen vacancies created by plasma etching were passivated by H termination. By utilizing hydrogen plasmas, we clarified the recovery efficiency by optical and stoichiometrical improvements with respect to the balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This can contribute to the positive effect of the hydrogen plasma exposure on the n-GaN. Surface defects on the device's n-side caused by dry etching can be passivated by hydrogen termination, 33) improving the quality of the n-contact. We can quantify it by comparing the voltage drop across the device with the selected injection current density.…”
mentioning
confidence: 99%
“…This can contribute to the positive effect of the hydrogen plasma exposure on the n-GaN. Surface defects on the device's n-side caused by dry etching can be passivated by hydrogen termination, 33) improving the quality of the n-contact. We can quantify it by comparing the voltage drop across the device with the selected injection current density.…”
mentioning
confidence: 99%
“…On the other hand, it is reported that Ga droplets are produced by heating in a hydrogen atmosphere 24) or Ar/N 2 plasma treatment, 25) and that nitrogen is desorbed in hydrogen plasma treatment. 26) It is also reported that H 2 plasma treatment of a SnO 2 substrate produces spherical Sn droplets on the surface. 27,28) Therefore, there is a possibility that the Ga droplets shown in Fig.…”
mentioning
confidence: 95%
“…[7][8][9][10][11] Thus, to ensure excellent material properties and provide high-performance devices, it is strongly required that the damage induced by plasma etching should be reduced or prevented. [12][13][14] Thermal annealing of GaN has been investigated for the recovery or improvement of the optical and electrical performance, and many researchers have reported that thermal annealing can recover the original material properties after process-induced damage. [15][16][17] However, if Ga-N bonds are broken during plasma etching processes at room temperature, then nitrogen is preferentially lost due to its high vapor pressure, which results in a gallium-rich surface.…”
mentioning
confidence: 99%